Tinjauan Pustaka: Intervensi Latihan Fisik pada Ibu Postpartum dengan Diastasis Recti Abdominis - Manda Aulia; Kartika Adyani (Universitas Islam Jember, 2026)
The postpartum period is the most crucial phase for mothers after giving birth. One of the problems that can arise is diastasis recti abdominis, which causes instability in the torso and pelvis, leading to symptoms such as abdominal pain, back pain, and hip pain. Treatment of diastasis recti abdominis with physical exercise is believed to reduce adverse effects and provide benefits for postpartum mothers. This study aims to analyze the intervention of abdominal rectus diastasis in postpartum mothers as a treatment for abdominal rectus diastasis. Literature search through databases such as PubMed and Google Scholar, with a publication period of 2022-2026. The inclusion criteria were articles in English, Indonesian, open access, experimental approach, traditional exercise intervention, and from accredited or indexed journals. Hypopressive and conventional abdominal exercises, split tummy exercises, plank exercises, belly binding and abdomen exercises, and postpartum exercises are effective in reducing rectus diastasis in postpartum women. In addition, curl-up exercises have a positive effect on the strength and thickness of the abdominal muscles of postpartum women with diastasis recti.